Design, implementation and testing of multi-energy infrastructures the multi agent way in Agent.HyGrid - Linnenberg, Tobias; Wassermann, Erik; Fay, Alexander; Derksen, Christian; Unland, Rainer; Oerter, Christian; Ludwig, Marcel; Zdrallek, Markus; Heldmaier, Wolfram; Stiegler, Martin (2016 IEEE International Energy Conference 2016, 2016)
Adaptation models; Agent.HyGrid project; Computational modeling; Context; Control Engineering; decentralized decision making; electrical power; energy markets; future energy grids exhibit; hybrid hardware test-beds; hybrid power systems; hybrid software test-beds; multiagent systems; multi-agent systems; multienergy infrastructure testing; power engineering computing; power markets; program testing; Simulation; Software; software artifacts; software development processes; software reusability; Systematics; Testing